Bivalent ligand MCC22 potently attenuates nociception in a murine model of sickle cell disease. Issue 7 (July 2018) - Cataldo, Giuseppe; Lunzer, Mary M.; Olson, Julie K.; Akgün, Eyup; Belcher, John D.; Vercellotti, Gregory M.; Portoghese, Philip S.; Simone, Donald A.
Abstract : Abstract: Sickle cell disease (SCD) is a chronic inflammatory disorder accompanied by chronic pain. In addition to ongoing pain and hyperalgesia, vaso-occlusive crises–induced pain can be chronic or episodic. Because analgesics typically used to treat pain are not very effective in SCD, opioids, including morphine, are a primary treatment for managing pain in SCD but are associated with many serious side effects, including constipation, tolerance, addiction, and respiratory depression. Thus, there is a need for the development of novel treatments for pain in SCD. In this study, we used the Townes transgenic mouse model of SCD to investigate the antinociceptive efficacy of the bivalent ligand, MCC22, and compared its effectiveness with morphine. MCC22 consists of a mu-opioid receptor agonist and a chemokine receptor-5 (CCR5) antagonist that are linked through a 22-atom spacer. Our results show that intraperitoneal administration of MCC22 produced exceptionally potent dose-dependent antihyperalgesia as compared to morphine, dramatically decreased evoked responses of nociceptive dorsal horn neurons, and decreased expression of proinflammatory cytokines in the spinal cord. Moreover, tolerance did not develop to its analgesic effects after repeated administration. In view of the extraordinary potency of MCC22 without tolerance, MCC22 and similar compounds may vastly improve the management of pain associated with SCD. Abstract : MCC22 potently reduced hyperalgesia in sickle mice and was associated with decreased expression of proinflammatory cytokines in the spinal cord and responses of dorsal horn neurons.